Spinoza's challenge to Jewish thought : writings on his life, philosophy, and legacy - Schwartz, Daniel B., 1974- (Tauber Institute for the Study of European Jewry series (Unnumbered), 2019)
Arguably, no historical thinker has had as varied and fractious a reception within modern Judaism as Baruch (Benedict) Spinoza (1632-77), the seventeenth-century philosopher, pioneering biblical critic, and Jewish heretic from Amsterdam. Revered in many circles as the patron saint of secular Jewishness, he has also been branded as the worst traitor to the Jewish people in modern times. Jewish philosophy has cast Spinoza as marking a turning point between the old and the new, as a radicalizer of the medieval tradition and table setter for the modern. He has served as a perennial landmark and point of reference in the construction of modern Jewish identity. This volume brings together excerpts from central works in the Jewish response to Spinoza. True to the diversity of Spinoza's Jewish reception, it features a mix of genres, from philosophical criticism to historical fiction, from tributes to diary entries, providing the reader with a sense of the overall historical development of Spinoza's posthumous legacy